Analisis Aset Pemerintah Daerah Kota Bandung - Rahayu Kusumadewi; Veren Virginia (Department of Public Administration, 2018)
Local government assets are one of the elements of the regional government balance sheet. Asset informaton in the balance sheet, describes the conditons of economic wealth owned by the local government. However, in the Bandung City Revenue Management Agency SKPD report, there was a decrease in the absolute value of the asset component, namely in the account of fixed assets, current assets and total assets. The purpose of the study was to analyze assets in the BPPD Bandung financial statements after a change in nomenclature, and to find out how the financial condition of Bandung BPPD, the ability of Bandung BPPD fulfill its obligations, and any indcators underlying the declnei in assets using ratios, includng; (1) Liquidty Ratoi, (2) Solvability Ratoi; and (3) Debt Ratio. Using descriptive-qualitative methods. Data collection techniques used were observation, interviews, and documentation. The results of this study indcate that, after a change in nomenclature, changes in the basis of measurement underlying the preparation of financial statements, namely a combinaton of cash and accrual basis. The financial condition of the Bandung City BPPD 2016-2017, in fulfillng its oblgations in prime condition. Judging from financial ratios, in the form of liquidty ratios, solvency ratios, and debt ratios, Bandung BPPD has a very good value between the comparison of assets and liablities. The decrease in current assets was influenced by the increase in tax receivables. Thus, the increase in tax receivables affects the increase in allowance for tax receivables. This is caused by bad tax receivables. The decrease in fixed assets is affected by the transfer of fixed assets to other asset accounts. This is because the condition of fixed assets is damaged and is not feasible to be used as a fixed asset. Fixed assets that were severely damaged reached 11.3 M.